High prevalence of primary multidrug resistant tuberculosis in persons with no known risk factors. - Larissa Otero (Public Library of Science (PLoS), 2011)
Introduction In high multidrug resistant (MDR) tuberculosis (TB) prevalence areas, drug susceptibility testing (DST) at diagnosis is recommended for patients with risk factors for MDR. However, this approach might miss a substantial proportion of MDR-TB in the general population. We studied primary MDR in patients considered to be at low risk of MDR-TB in Lima, Peru. Methods We enrolled new sputum smear-positive TB patients who did not report any MDR-TB risk factor: known exposure to a TB patient whose treatment failed or who died or who was known to have MDR-TB; immunosuppressive co-morbidities, ex prison inmates; prison and health care workers; and alcohol or drug abuse. A structured questionnaire was applied to all enrolled participants to confirm the absence of these factors and thus minimize underreporting. Sputum from all participants was cultured on Löwenstein-Jensen media and DST for first line drugs was performed using the 7H10 agar method. Results Of 875 participants with complete data, 23.2% (203) had risk factors for MDR-TB elicited after enrolment. Among the group with no reported risk factors who had a positive culture, we found a 6.3% (95%CI 4.4-8.3) (37/584) rate of MDR-TB. In this group no epidemiological characteristics were associated with MDR-TB. Thus, in this group, multidrug resistance occurred in patients with no identifiable risk factors. Conclusions We found a high rate of primary MDR-TB in a general population with no identifiable risk factors for MDR-TB. This suggests that in a high endemic area targeting patients for MDR-TB based on the presence of risk factors is an insufficient intervention.